РОЗВИТОК НАУКОВИХ ЗАСАД ТА РОЗРОБКА ЗАСОБІВ ПІДВИЩЕННЯ ПОКАЗНИКІВ БЕЗВІДМОВНОСТІ ПОТУЖНИХ ТУРБО- І ГІДРОГЕНЕРАТОРІВ - Кенсицький, О.Г. (Інститут електродинаміки Національної академії наук України, 2019)
The analysis of generating equipment reliability of electric power plants of Ukraine is made. Indices of reliability and the main most damaged elements and parts of hydro- and turbogenerators, also possible condition and constructive factors of damages beginnings are determined. With help methods of systems analysis, mathematical and physical simulation, also natural experiment are made researches of electromagnetic, heat and thermomechanical processes features in equipment at beginnings of various physical character defects. Researchers are made for wide diapason of working modes at the different design of separate elements and parts. The maximum heating take place in an end packet under-slot zone under the conditions of reactive power consumption is proved. As a result of experimental investigations is determined, the load level and hydrogen temperature at the end of gas-coolers have an influence on a vibration state both machines in general and its separate parts. Vibration have maximum at the active load less nominal value, especially under the conditions of reactive power consumption, and low temperature of refrigerant. The comparative analysis of vibration force in stator turbogenerator with 1000 MW power in two-polar and four-polar implementation is made. It is determined while crossing to conditions of reactive power consumption in a spectrum of vibration exciting force in a stator two-polar turbogenerator there is increase of double frequency component of electromagnetic oscillation (200 Hz). Comparison of effectiveness the design of stator core end zone of a turbogenerator is made. The expediency and efficiency of use the electromagnetic internal distributed tooth-slot design shields are proved. The technical solutions of optimization the design of elements and parts turbo- and hydrogenerators – the schemes of end zone cooling and the system of stator core pressing, devices of frontal part fastening, also ventilation of slits in stator core teeth in accordance with results of researches are developed and scientific substantiation. References 7, figures 12.